Les droits et les obligations des époux : les régimes matrimoniaux - Groffier-Attala, Éthel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
Bill 69, which came intoforce on April the 2nd 1981 ; brought about important changes in the field of matrimonial regimes. The main ones, hereinafter examined, concern the withdrawal of community of moveables and acquests from the Civil code, the limits improved upon liberty of marriage convenants, the decline of matrimonial regimes as an institution due to the Judge's increased discretionary power, the procedure pertaining to a change of matrimonial regime and, finally, the modifications to the legal regime of partnership of acquests.